Grazing Exclusion Changed the Complexity and Keystone Species of Alpine Meadows on the Qinghai-Tibetan Plateau - Zhang, Yong; Gao, Qingzhu; Ganjurjav, Hasbagan; Dong, Shikui; Zheng, Qiuzhu; Ma, Yandan; Liang, Kemin (Frontiers in Ecology and Evolution, 2021)
Grazing exclusion is an effective approach to restore degraded grasslands. However, the effects of grazing exclusion on keystone species and the complexity of plant community were poorly investigated. Here, we conducted a field survey along a grazing exclusion gradient, i.e., Grazing, grazing exclusion below five years, grazing exclusion with five years, grazing exclusion with seven years and grazing exclusion over seven years, in alpine meadows on the central of Qinghai-Tibetan Plateau. The complexity and keystone species of alpine meadows were analyzed by network analysis. The results showed that 1) the species richness did not change, but aboveground biomass and the cover of the plant community trended to increase with the duration of grazing exclusion. 2) The contents of soil nutrients mainly remained stable, while the soil bulk density decreased with the duration of grazing exclusion. 3) There was a hump-shaped change of the complexity of the plant community along the grazing exclusion gradient. Moreover, the keystone species varied among different grazing exclusion treatments. Based on the complexity of the plant community and the changes of keystone species, the optimum duration of grazing exclusion for alpine meadows should be between five and seven years. Our results suggest that besides the productivity, the change of the complexity and keystone species of plant community should be considered when grazing exclusion is adopted to restore the degraded alpine meadows.